Saw at the Simonds Manufacturing Co. exhibit, Manufactures Building, Alaska Yukon Pacific Exposiition, Seattle, Washington, 1909 - University of Washington Libraries. Manuscripts, Special Collections, University Archives Division (1909)
PH Coll 777.x.Advert.11 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number